Adiponectin and Chemerin: Contrary Adipokines in Regulating Reproduction and Metabolic Disorders. (October 2018) - Singh, Anusha; Choubey, Mayank; Bora, Puran; Krishna, Amitabh
Metabolic disorders such as obesity and type 2 diabetes are one of the most familiar risk factors in the present time among every age-group. It is associated with altered levels of adipokines such as adiponectin, chemerin, leptin, resistin, visfatin, and so on. Adiponectin is one of the adipocyte-specific protein with novel applications pertaining to metabolism by promoting insulin sensitivity and regulating glucose and fatty acid catabolism, while chemerin is considered as an inhibitor of insulin signaling and glucose catabolism. Other than these established functions, both the adipokines are intimately involved in coordinating reproductive activities, but they exhibit contrary functions. This review is an amalgamation of recent information related to adiponectin and chemerin in male and female reproduction and further its association with metabolism-related reproductive disorders. The direct effect of adiponectin and chemerin on various reproductive parameters has been investigated, but there was a rampant failure to account for in vivo data which gives a broad outlook on the regulatory mechanism of both adiponectin and chemerin related to male and female reproductive functions. Adiponectin is known to promote gonadal activities, while chemerin exerts antigonadal actions. Recent research suggests that high chemerin/low adiponectin ratio plays a vital role in causing dyslipidemia and metabolic syndrome in patients. The dysregulated ratio of adiponectin to chemerin during various metabolic disorders makes it really worthy in relation to an application for therapeutics. Still, a lot regarding both the adipokines has to be explored and brought forward in order to deal with therapeutics of metabolism-related reproductive disorders.